2022
DOI: 10.1177/23259671221102478
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Pediatric Gymnastics Injuries Reported in US Emergency Departments: Sex- and Age-Based Injury Patterns

Abstract: Background: Despite increasing participation rates in youth gymnastics, the majority of epidemiologic literature focuses on older elite athletes or stratifies athletes by level of competition. Hypothesis: The authors hypothesized that sex- and age-based patterns in youth gymnastics–related injuries exist, which are otherwise overlooked in an unstratified population. Study Design: Descriptive epidemiology study. Methods: Publicly available injury data from the National Electronic Injury Surveillance System were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Relevant studies have shown that there is a positive correlation between muscle strength and the level of socioeconomic development (Drenowatz et al, 2020). In terms of standing long jump performance, which reflects lower limb muscle strength, overall boys' standing long jump performance was higher than girls', which is consistent with the findings of several studies (Castro‐Pinero et al, 2009; Tisano et al, 2022; Zhang et al, 2021). In terms of different high‐altitude regions, overall Tibetan adolescents in Shigatse region had the lowest standing long jump scores.…”
Section: Discussionsupporting
confidence: 89%
“…Relevant studies have shown that there is a positive correlation between muscle strength and the level of socioeconomic development (Drenowatz et al, 2020). In terms of standing long jump performance, which reflects lower limb muscle strength, overall boys' standing long jump performance was higher than girls', which is consistent with the findings of several studies (Castro‐Pinero et al, 2009; Tisano et al, 2022; Zhang et al, 2021). In terms of different high‐altitude regions, overall Tibetan adolescents in Shigatse region had the lowest standing long jump scores.…”
Section: Discussionsupporting
confidence: 89%
“…Another study on pediatric gymnastics revealed that young athletes, particularly female athletes, were prone to wrist and lower arm fractures and upper extremity injuries in childhood rather than adolescence. Furthermore, both male and female adolescents had an increase in the occurrence of concussions, as well as foot and ankle injuries [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies tended to explore the in uence of additional variables and the impact on SRC incidence, such as chronic headaches, medications, environmental altitudes, and different eld tur ng environments. Additionally, multiple studies investigating incidence across multiple sports reported that SRC incidence was higher in adolescents compared to children [50][51][52] and females had a higher risk of SRC than males [53,54].…”
Section: Qualitative Synthesismentioning
confidence: 99%